A dynamical system perspective on mathematical programming. Issue 2 (3rd April 2018) - Pedregal, Pablo
ABSTRACT: We explore how to build a vector field from the various functions involved in a given mathematical programme, and show that equilibria of the corresponding dynamical system are precisely the solutions of the underlying optimality conditions for the original optimization problem. The general situation in which explicit inequality constraints are present is especially interesting as the vector field has to be discontinuous, and so one is led to consider discontinuous dynamical systems and their equilibria.